Intersecting challenges and ways forward: The impact of the COVID-19 pandemic on an urban First Nations community in Southern Ontario, Canada - Eric N. Liberda; Fatima Ahmed; Nicholas D. Spence; Sarah Plain; Robert J. Moriarity; Leonard J. S. Tsuji; Nadia A. Charania (PLoS ONE, 2025)
The COVID-19 pandemic has had wide-ranging impacts on communities worldwide, with Indigenous communities in southern Ontario, Canada, being no exception. Partnering with Aamjiwnaang First Nation, we explored the multifaceted impacts of the pandemic and learnings for the future. This study utilized semi-structured interviews with the community’s pandemic committee and other front line essential services (N = 12) to explore the nuanced dimensions of the pandemic’s effects. Data were analysed using a template approach to codebook thematic analysis to examine various aspects of the pandemic response. Five main themes were identified, including: (i) Wellbeing and mental health, (ii) Work-life balance, (iii) Community and social factors, (iv) Organizational dynamics, and (v) Lessons learned and future planning. Our findings unveiled a multifaceted spectrum of challenges, encompassing socioeconomic, psychological, and organizational aspects, which the First Nations community encountered amidst the pandemic. Despite these challenges, the commitment to community adaptation and collaboration highlighted the resilience cultivated through strong Indigenous leadership, trusting partnerships, and transparent communication, contributing to an effective response. This research stresses the need for future pandemic preparedness efforts to prioritize Indigenous leadership and address the social and cultural determinants of Indigenous health. Additionally, to effectively address future environmental and health emergencies, there is a pressing need to adopt an all-hazards approach and develop comprehensive, yet adaptable plans tailored to meet the diverse needs of communities.